Effect of supplementation of Turmeric, Black pepper and their combination as phytogenic feed additive on carcass characteristics and organoleptic parameters of Japanese quail: doi: 10.5958/2581-6616.2021.00003.7 - Kumar, V. D. Santhosh; Nath, Narendra; K, K. Naga Raja Kumari.; Kumar, D. Srinivas; T , T. Keerthana (Journal of Meat Science, 2022)
Day-old quail chicks (N=150) were distributed randomly into five treatments with three replicates containing ten birds each and fed with five experimental diets T1 (Basal diet), T2 (Basal diet supplemented with 0.75% turmeric), T3 (Basal diet supplemented with 1% black pepper), T4 (Basal diet supplemented with 0.25% turmeric and 0.5% black pepper) and T5 (Basal diet supplemented with 0.5% turmeric and 1% black pepper). Carcass traits like mean dressing percentage, weights of liver, heart, and gizzard did not show any significant difference among the treatment groups. The sensory evaluation scores were improved significantly (p<0.05) pertaining to juiciness, tenderness, and overall acceptability when compared with the control and the highest score for overall acceptability was observed in the group provided with a combination of turmeric (0.25%) and black pepper (0.50%) at a low level. Based on this study it can be concluded that a combination of turmeric and black pepper are more useful in improving the meat acceptability than individual supplementation in quail diets.